Evaluation Of Anti-Hyperlipidemic Activity Of Ethanolic Extract Of Stem Bark Of Acacia Ferruginea In High Fat Diet-Induced Hyperlipidemic Rats (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2024)
This study evaluates the anti-hyperlipidemic activity of ethanolic extract from the stem bark of Acacia ferruginea in high-fat diet-induced hyperlipidemic Wistar rats. The experimental model involved administering graded doses of the extract and comparing its effects with a standard reference drug, Atorvastatin. The study demonstrated that the ethanolic extract significantly reduced serum triglycerides, total cholesterol, low-density lipoprotein (LDL), and very-low-density lipoprotein (VLDL) levels while increasing high-density lipoprotein (HDL) levels in a dose-dependent manner.  The findings highlight the potential of Acacia ferruginea as a natural therapeutic agent for managing hyperlipidemia and associated cardiovascular risks.